The Relationship Between Personality Types And General Health With Job Satisfaction Of Yazd Health Center Staffs - Ali Reza Bakhshayesh (Tehran University of Medical Sciences, 2013)
Background and Aim: One of the effective factors on staffs' job satisfaction is their general health and personality types. This study is aimed to study the relationship between general health and personality types with the staffs' job satisfaction .  Materials and Methods: Seventy One women and men employee, aged 21 to 56 years working at Yazd health center were examined with full enumeration and by using General Health Questionnaire(GHQ), Job Descriptive Index(JDI) and the five-factor personality inventory(NEO). Research method was descriptive-correlation type and data were analyzed by using statistical tests like Pearson correlation, independent t test, ANOVA and stepwise regression.  Results: The results showed that the relationship of the staffs' general health with their neuroticism was direct (r=0/542) and with extraversion and agreeableness was reverse(r=-0/38, -0/34). But, it was not correlated with flexibility and responsibility . General health is inversely related to the three job satisfaction components(nature of work, job promotion, salary & job satisfaction total score) and it was irrelevant with the satisfaction of coworkers and supervisors. Lower general health was associated with neuroticism and good general health was associated with extraversion and agreeableness. Lower general health was also associated with lower job satisfaction and vice versa. Also there was a correlation between nature of work satisfaction and extraversion(p=0/01).  Conclusion : We conclude that by decreased or increased general health of staffs and effect of their personality traits, job satisfaction would decrease or increase. Many cause decreased or increased of job satisfaction